1115 NON-INVASIVE MYOCARDIAL WORK INDICES IN PATIENTS WITH FONTAN CIRCULATION. (15th December 2022) - Pozza, Alice; Sabatino, Jolanda; Cuppini, Elena; Cerutti, Alessia; Biffanti, Roberta; Reffo, Elena; Castaldi, Biagio; Sirico, Domenico; Fumanelli, Jennifer; Di candia, Angela; Basso, Alessia; Di Salvo, Giovanni
Abstract: Background: Although the Fontan operation has contributed greatly to the improvement of survival in patients with a single ventricle, cardiac function and exercise capacity may deteriorate over time. However, there have been no quantitative analyses of the effects of Fontan circulation on myocardial work (MW). Recently, a novel non-invasive method for calculating MW has been introduced on the basis of speckle tracking analysis with the estimation of left ventricular (LV) pressure from brachial artery cuff pressure. Purpose: Aim of this study was to evaluate the diagnostic performance of the non-invasive myocardial work indices in predicting subclinical myocardial work impairment in Fontan patients. Methods: A total of 69 patients were included and compared with healthy age- and sex- matched controls (CTRL). Ventricular systolic function and global longitudinal strain (GLS) were assessed. Cardiopulmonary exercise test was performed. Global myocardial work index (MWI) was calculated as the area of the LV pressure strain loops. From MWI, global constructive work (MCW), wasted work (MWW) and work efficiency (MWE) were estimated. Results: The two groups were comparable for blood pressure, weight and height. Mean age of Fontan patients was 21.0±9.2 years. MWI (1162 ± 364 mmHg% vs 1777 ± 240 mmHg%, p < 0.001), MCW (1554 ± 450 mmHg% vs 2102 ± 221 mmHg%, p = 0.001) and MWE (90 ± 6% vs 96 ± 2% p = 0.001) were significantly reduced in Fontan patients compared with healthy CTRL. Moreover, GLS (-13, 9 ± 3, 1% vs -21, 2 ± 1.5%, p < 0.001) and the ejection fraction (EF) (58, 9 ± 4.5% vs 63.3 ± 3.9%, p < 0.002) were significantly lower in Fontan patients. Fontan patients with normal EF showed, however, significantly reduced values of MWI compared with CTRL (p<0.05). Fontan patients with functional right ventricle showed significantly reduced MWE compared with patients with functional left ventricle (p=0.030). In univariate analysis, peak VO2 was significantly associated with age, SatO2, MWI. In multivariate regression, lower peak VO2 was associated with older age (p = 0.003) and lower MWI (p = 0.026). Conclusions: Fontan physiology is associated with disadvantageous ventricular work. In Fontan patients, estimation of MWI may be a more sensitive indicator of myocardial work impairment compared with EF and is able to predict exercise capacity.